Uptake and Intracellular Fate of Peptide Surface‐Functionalized Silica Hybrid Magnetic Nanoparticles In Vitro. (8th September 2014) - Digigow, Reinaldo G.; Vanhecke, Dimitri; Rothen‐Rutishauser, Barbara; Clift, Martin J.D.; Petri‐Fink, Alke
<x xml:space="preserve">Abstract</x> Recently, the use of nanomaterials as intracellular targeting tools for theranostics has gained heightened interest. Despite the clear advantages posed by surface‐functionalized nanoparticles (NPs) in this regard, limited understanding currently exists due to difficulties in reliably synthesizing NPs with surface functionalizations adequate for use in such applications, as well as the manner of analytics used to assess the cellular uptake and intracellular localization of these NPs. In the present study, two key surface functionalities (a nuclear localization sequence (NLS) and integrin‐ligand (cRGD)) are attached to the surface of multifunctional, silica hybrid magnetic nanoparticles (SHMNPs) containing a polyethylene glycol (PEG) polymer coating using a well‐described, reliable, and reproducible microreactor set‐up. Subsequent analytical interpretation, via laser scanning confocal, transmission electron and dark‐field microscopy, as well as flow cytometry, of the interaction of SHMNPs‐PEG‐cRGD‐NLS with macrophage (J774A.1) and epithelial (HeLa) cells shows internalization of the SHMNPs‐PEG‐cRGD‐NLS in both cell types up to 24 h after 20 μg mL−1 exposure, as well as increasing aggregation inside of vesicles over this time period. The findings of this study show that by incorporating a variety of state‐of‐the‐art analytical and imaging approaches, it is possible to determine the specific effectiveness of surface peptide and ligand sequences upon multifunctional SHMNPs.